The Influence of Organizational Culture and Competency on Employee Performance Development with Job Satisfaction as a Mediation Variable (Study at Pt. Bpr Nbp 20 Delitua) - Berutu, Damelia Putri; Karim, Ahmad; Rambe, Saima (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to determine how organizational culture and competence influence employee performance development with job satisfaction as a mediating variable at PT. BPR NBP 20 Delitua. The object of this study was employees of PT. BPR NBP 20 Delitua with 30 respondents. Quantitative methods were used in the study using multiple linear analysis techniques, validity tests, reliability tests, and classical assumption tests. As well as hypothesis testing using t-test, f-test, r-test and mediation tests where the data were processed using SPSS. The results of the t-test study, obtained a calculated t value> t-table value, which is 3.126> 2.052, and a significant value <0.05, which is 0.000 <0.05 so that it is concluded that organizational culture (X1) has a positive and significant effect on performance development (Y), H1 is accepted. Organizational culture (X1) has a positive and significant effect on job satisfaction (Z), with a calculated t value > t table value, which is 4.945 > 2.052, and a significant value < 0.05, which is 0.000 < 0.05, so H2 is accepted. Competence (X2) has a positive and significant effect on performance development (Y), with a calculated t value > t table value, which is 3.638 > 2.052, and a significant value < 0.05, which is 0.000 < 0.05, so H3 is accepted. Competence (X2) has a positive and significant effect on job satisfaction (Z), with a calculated t value > t table value, which is 3.133 > 2.052, and a significant value < 0.05, which is 0.004 < 0.05, so H4 is accepted. Job satisfaction (Z) has a positive and significant effect on performance development (Y) with a calculated t value > t table value, which is 4.421 > 2.052, and a significant value <0.05, which is 0.000 <0.05 so that H5 is accepted. The results of the f test analysis, obtained a calculated f value > f table value, which is 50.849 > 3.354 and a significance of 0.000 <0.05, so it is concluded that organizational culture (X1) and competence (X2) together have a positive and significant effect on work development (Y), H6 is accepted. The results of the Sobel test obtained a calculated t value of 7.563 > t table 2.052 so that it can be concluded that job satisfaction (Z) is able to mediate the influence of organizational culture (X1) and competence (X2) on employee performance development (Y) at PT. BPR NBP 20 Delitua. Keywords: Competence, Employees, Organizational Culture, Performance